Więź zrzeszeniowa skazanych ze środowiskiem a perspektywa działań resocjalizacyjnych - Muskała, Maciej (Wydawnictwo Naukowe UAM, 2009)
Abstrakt Actually observing the raising number of prison population, cause in a big matter as a result of punishment system, demand to make up a lot of different remeding actions. They should concentrate both on leading to the system some number of a new sanctions, sanctions about non- isolation character. As well as intensification of penitentiary affection, and also this, that main duty is to develop offenders bonds with society, that make easier the process of readaptation after left the prison. In this study we analyse one of the bonds which offender refer, namely association bond.
Keywords: więź społeczna; więź zrzeszeniowa; kara pozbawienia wolności; skazani